4D Imaging of Mineral Dissolution in Porous Carbonado Diamond: Implications for Acid Digestion and XCT Measurement of Porosity and Material Properties - Eckley, Scott A.; Ketcham, Richard A. (Frontiers in Earth Science, 2019)
In this study, we utilize high-resolution X-ray computed tomography (XCT) to track the progress of a leaching process within a pore network. Dissolution and leaching are difficult processes to observe with combined temporal and spatial context, particularly when dissolving material within a non-reactive pore network, and XCT is a uniquely suited technique for observing dissolution in situ, and extracting quantitative data on pore networks and the material in them in 3D. We XCT image two samples of porous diamond (carbonado) during a sequential acid leaching procedure designed to remove a diverse assemblage of pore-filling minerals. This experiment provides a unique perspective for observing mineral dissolution in 4D, allowing us to identify differences in mineral inclusions and pore network topology between carbonado samples based on dissimilar dissolution styles and rates. We are also able to observe the formation of fluorides during acid digestion, which can persist throughout acid leaching procedures and drastically affect yields for geochemical measurements of certain elements, most importantly REEs, U, Th, and Pb. We test various approaches to measuring porosity, finding that methods based on quantitative interpretation of CT numbers as partial porosity give more accurate results than purely binary segmentation, and that attempts to segment the pore network using visual criteria are scattered and unreliable. We document how image quality can be locally affected by material properties, with filled pores measurably blurrier than empty ones. Such local variation in point-spread function is important when segmenting XCT data for the purposes of quantification. Finally, we demonstrate that by comparing mass and X-ray attenuation loss it is possible to estimate the relative heavy-metal content of the leached material.